2010
DOI: 10.1111/j.1398-9995.2009.02252.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles of IL‐17A and IL‐25 in the regulation of TSLP production in human nasal epithelial cells

Abstract: Our study provides the first evidence that both IL-17F and IL-25 can be induced by dsRNA in HNECs. Despite of the opposing effects of IL-17A and IL-25 on TSLP regulation in HNECs, IL-25 was dominant to IL-17A, providing a plausible explanation for the simultaneous upregulation of IL-17 cytokines and TSLP in patients with AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 33 publications
(57 reference statements)
3
63
2
2
Order By: Relevance
“…Three ligands, IL-17A, IL-17F, and IL-25, have been reported capable of signaling through IL-17RA [34]. Previous report demonstrated that IL-17F and IL-25 played opposing roles of IL-17A in the regulation of lymphopoiethin production in human nasal epithelial cells [35]. Our study found that IL-17F was also elevated in BALF of mice infected with BJ501 live virus ( Figure 6B).…”
Section: Discussionsupporting
confidence: 66%
“…Three ligands, IL-17A, IL-17F, and IL-25, have been reported capable of signaling through IL-17RA [34]. Previous report demonstrated that IL-17F and IL-25 played opposing roles of IL-17A in the regulation of lymphopoiethin production in human nasal epithelial cells [35]. Our study found that IL-17F was also elevated in BALF of mice infected with BJ501 live virus ( Figure 6B).…”
Section: Discussionsupporting
confidence: 66%
“…Quantitative Real-time PCR (qPCR)-The qPCR was performed as previously described (22,23). In brief, total RNA was extracted from HUVECs by TRIzol Reagent (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…The IL-17E level is higher in nasal lavages from allergic rhinitis patients than normal controls. 148 Upon allergen challenge, IL-17E is increased in the bronchial mucosa of asthmatic patients and the skin dermis of atopic subjects. 149 Consistently, IL-17E mRNA is increased in the airways of antigen-challenged mice.…”
Section: Il-17dmentioning
confidence: 99%